Haemodynamic responses to intubation, extubation and post‐operative analgesia after intravenous lignocaine in laparoscopic cholecystectomy surgeries: a randomized control study - gujja, srikanth; Arora, Varun; Yelagandula, Sravanthi; Bhandari, Chanchal; Jeevanbabu, Mittapalli (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: To evaluate the effect of intravenous lignocaine on haemodynamic responses to intubation, extubation and post‐operative analgesia in laparoscopic cholecystectomy surgeries. Methods: This prospective, randomized, double blinded study was conducted in patients for elective laparoscopic cholecystectomy surgery in tertiary care hospital of Tamil Nadu. Group A (n=60) received 0.9% normal saline for perioperative intravenous infusion and Group B (n=60) received preservative free lignocaine 2% (20mg/ml) as intravenous infusion Hemodynamic responses were recorded to intubation, extubation and post‐operative analgesia in both groups. VAS scores and pain free period were also compared. Results: Pulse rate (PR) and mean arterial pressure (MAP) were significantly increased in both the groups during laryngoscopy and intubation, though the rise of both in lignocaine group was significantly less than normal saline group. (p<0.0001) Similarly, both PR and MAP were significantly increased during extubation in both the groups. (p<0.0001) However, the rise of both the parameters in lignocaine group was significantly less as compared to normal saline group. (p<0.0001) VAS scores in immediate post operative period were better in lignocaine group than normal saline group. The mean pain free period was less than an hour in normal saline group, while it was approximately 4 hours in lignocaine group. (p<0.0001) Conclusions: This study concluded that i.v infusion of lignocaine had significantly increased the pain free period post operatively. So those who are not affordable for epidural block, lignocaine i.v infusion is better alternative for post operative analgesia.